The use of Edmodo by supervisor to improve professional competence of Islamic Education teachers - Abidin Sholeh (Prodi PGMI IAIN Salatiga, 2018)
This study aims to find out the implementation of Edmodo platform in clinical supervision to improve professional competence of The Islamic Education teacher of Elementary School (SD) in Salatiga in 2017. This research used the action research method. Data retrieval techniques were through observation and interview with descriptive analysis. The results of this study concluded that; First, the average result of observation cycle 1 in stage 1 is 62.32 and in stage 2 is 66.80 with progress increase 4.48 with category A is 1 person, category B is 8 people, category C is 2 people. Secondly, the average result of observation of cycle 2 in stage 1 is 76.52 and 84.40 in stage 2, with progress increase 7.88 with category A is 10 people and category B is 1 person. Third, the implementation of the Edmodo platform in clinical supervision can be used to improve the professional competence of The Islamic Education teacher of elementary school by considering the average score level of 65.19 which means that the score is capable of performing clinical supervision to improve the professional competence of The Islamic Education teacher of elementary school.